Type-3 Feistel Network of The 128-bits Block Size Improved Blowfish Cryptographic Encryption - Ashwaq T. Hashim (Engineering and Technology Journal, 2009)
In this paper, a new secret-key block cipher called 128-bits Blowfish isproposed which is an evolutionary improvement of 64-bits Blowfish designed tomeet the requirements of the Advanced Encryption Standard (AES) to increasesecurity and to improve performance. The proposed algorithm will be used avariable key size up to 192 bytes. It is a Type-3 Feistel network iterated simplefunction 16 times. Specifically, in this proposed algorithm, a combination of fourS-boxes lookups, multiplications as well as fixed and data-dependent rotations willbe used. Mixing round provide different levels of security, efficiency, flexibilityand good avalanche effect. The proposal is word-oriented, in that all the internaloperations are performed on 32-bit words. So it is possible to implement thealgorithm on smart cards efficiently.